Conceptual Refactoring for Creative Information Retrieval - Veale, Tony (Theoria et Historia Scientiarum, 2008)
Information retrieval (IR) is an effective mechanism for text management that has received widespread adoption in the world at large. But it is not a particularly creative mechanism, in the sense of creating new conceptual structures or refactoring existing ones to pull in documents that describe, in novel and inventive ways, a user’s information needs. Since language is a dynamic and highly creative medium of expression, the concepts that one seeks will therefore represent a moving target for IR systems. We argue that only by thinking creatively, and viewing concepts as fluid meaning structures capable of dynamic reorganization, can an IR system effectively retrieve documents that express themselves creatively.